L’incendio del Campidoglio e la fine del saeculum etrusco - Mastrocinque, Attilio (Gerión. Revista de Historia Antigua, 2005)
In the years 91 to 82 BCE Italy had to suffer because of a series of civil and external wars. People believed that the entire world was upset in occasion of the birth of a new saeculum, as the Etruscan soothsayers were forecasting. A very deep crisis of institutions and social system was in progress, which let people believe that the socialsystem of the polis had to fail. Pompey’s efforts could give new trust in the Toman political and social system, for which Posidonius gave a new ethical interpretation